An ethnobotanical analysis of parasitic plants (Parijibi) in the Nepal Himalaya. Issue 1 (December 2016) - O'Neill, Alexander; Rana, Santosh
Abstract Background Indigenous biocultural knowledge is a vital part of Nepalese environmental management strategies; however, much of it may soon be lost given Nepal's rapidly changing socio-ecological climate. This is particularly true for knowledge surrounding parasitic and mycoheterotrophic plant species, which are well represented throughout the Central-Eastern Himalayas but lack a collated record. Our study addresses this disparity by analyzing parasitic and mycoheterotrophic plant species diversity in Nepal as well as the ethnobotanical knowledge that surrounds them. Methods Botanical texts, online databases, and herbarium records were reviewed to create an authoritative compendium of parasitic and mycoheterotrophic plant species native or naturalized to the Nepal Central-Eastern Himalaya. Semi-structured interviews were then conducted with 141 informants to better understand the biocultural context of these species, emphasizing ethnobotanical uses, in 12 districts of Central-Eastern Nepal. Results Nepal is a hotspot of botanical diversity, housing 15 families and 29 genera of plants that exhibit parasitic or mycoheterotrophic habit. Over 150 of the known 4500 parasitic plant species (~3 %) and 28 of the 160 mycoheterotrophic species (~18 %) are native or naturalized to Nepal; 13 of our surveyed parasitic species are endemic. Of all species documented, approximately 17 % of parasitic and 7 % of mycoheterotrophic plants have ethnobotanical uses as medicine (41 %), fodder (23 %), food (17 %), ritual objects (11 %), or material (8 %). Conclusions Parasitic and mycoheterotrophic plant species exhibit high diversity in the Nepal Central-Eastern Himalaya and are the fodder for biocultural relationships that may help inform future environmental management projects in the region.